2023
DOI: 10.1098/rspb.2022.2068
|View full text |Cite
|
Sign up to set email alerts
|

The price of defence: toxins, visual signals and oxidative state in an aposematic butterfly

Abstract: In a variety of aposematic species, the conspicuousness of an individual's warning signal and the quantity of its chemical defence are positively correlated. This apparent honest signalling is predicted by resource competition models which assume that the production and maintenance of aposematic defences compete for access to antioxidant molecules that have dual functions as pigments and in protecting against oxidative damage. To test for such trade-offs, we raised monarch butterflies ( Danaus plex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 83 publications
2
14
0
Order By: Relevance
“…Phenotypic variation in aposematic signals is puzzling because predators avoid defended prey that are common but attack rarer ones (Müller 1878). Trade-offs in resource allocation have been suggested to account for some of the variation found in natural aposematic populations (Wang, 2011; Burdfield-Steel et al, 2019; Blount et al, 2023). However, the phenotypic correlations between primary and secondary defences do not necessarily prove this connection, as interactions between such complex traits can be shaped by genetic correlations, pleiotropic effects or simply variable environmental conditions (e.g., food availability, environmental stochasticity, presence of predators).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic variation in aposematic signals is puzzling because predators avoid defended prey that are common but attack rarer ones (Müller 1878). Trade-offs in resource allocation have been suggested to account for some of the variation found in natural aposematic populations (Wang, 2011; Burdfield-Steel et al, 2019; Blount et al, 2023). However, the phenotypic correlations between primary and secondary defences do not necessarily prove this connection, as interactions between such complex traits can be shaped by genetic correlations, pleiotropic effects or simply variable environmental conditions (e.g., food availability, environmental stochasticity, presence of predators).…”
Section: Discussionmentioning
confidence: 99%
“…A study on the Asian lady beetle, Harmonia axyridis , found no phenotypic correlation between the reflex bleeding response (frequency of secretion of the defensive chemicals) and the beetle colouration, even though reflex bleeding is costly and affects life-history traits (Grill and Moore, 1998). Recent work on monarch butterflies Danaus plexippus showed a link between toxin sequestration and warning signals, with male conspicuousness inversely correlated with oxidative damage (due to an increase in concentrations of sequestered cardenolides) (Blount et al, 2023). Previous work by Lindstedt et al, (2010) showed that the aposematic, generalist herbivore Arctia plantaginis (hereafter referred to as the wood tiger moth) develops a paler, orange warning signal when reared on Plantago lanceolata with high concentrations of iridoid glycosides (IG) compared to the more conspicuous, dark red warning signal of individuals fed on a strain of the same plant with low concentrations of IG.…”
Section: Introductionmentioning
confidence: 99%
“…In Blount et al's ( 2009 ) resource competition framework, pigments that are used in prey warning signals play a role both in producing the signal and in preventing self‐damage when storing toxins (due to their antioxidant properties). When antioxidants are required to enable high levels of toxicity, then the most toxic species are predicted to be the most conspicuous because they gain access to more antioxidants (or are genetically disposed to produce more), than those that are less bright and less toxic (see figure 1 in Blount et al, 2023 ). There are many critiques of the idea that warning signals are costly, one of which is that it is unclear whether warning signals ‘use up’ resources that are needed to produce chemical defenses (Guilford & Dawkins, 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many critiques of the idea that warning signals are costly, one of which is that it is unclear whether warning signals ‘use up’ resources that are needed to produce chemical defenses (Guilford & Dawkins, 1993 ). The potential influence of antioxidant availability and oxidative stress on the development of aposematic displays has received limited empirical attention (Ojala et al, 2005 ; Sandre et al, 2007 ), though Blount et al ( 2023 ) found that monarch butterflies ( Danaus plexippus ) that sequestered higher concentrations of chemical defense experienced higher levels of oxidative damage, and monarchs with lower oxidative damage allocated more resources to color and toxicity than monarchs with higher oxidative damage. Because Blount et al ( 2023 ) reared monarchs on different milkweed hostplants ( Apocynaceae ) to manipulate the amounts of toxins the butterflies sequestered, and because different hostplants vary in many traits (not just chemical defense), the costs that Blount et al ( 2023 ) detect may not result only from varied sequestration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation